Ultrastructural Changes in Malva sylvestris Leaves in Response to Aqueous Sulfur Dioxide - M. Akbar*, B. Minu, A. Shajrul, S. Rakashanda and (Journal of Phytology, 2011)
Leaf discs of Malva sylvestris were treated with different concentrations of aqueous sulfur dioxide (10-1000ppm) for four hours under illumination (500W tungsten bulb). Scanning electron microscopy was used to determine the extent of damage to the ultra structure of Malva sylvestris under sulfur dioxide exposure. Slight opening of stomata was observed at 100 ppm exposure and at 1000 ppm concentration of aqueous sulfur dioxide well pronounced opening of stomata was found, mesophyll cell collapse associated with cellular disorganization and plasmolysis was also observed.